THE ROLE OF BUSINESS INCUBATOR RESOURCES IN FACILITATING THE DEVELOPMENT OF NEW VENTURES: AN EMPIRICAL RESEARCH IN INDONESIA - Fajri, Detha Alfrian (Faculty of Administrative Science, Universitas Brawijaya, 2023)
The purpose of this research is to highlight the role of business incubator resources in facilitating internal-external networking and entrepreneurial orientation towards new venture performance. This study employs an explanatory research design and a quantitative approach to elucidate the causal relationships between variables. The research sample consists of 96 founders or co-founders of startups affiliated with business incubators. Data analysis was conducted using SmartPLS-structural equation modeling (SEM). The findings of this study indicate that business incubator resources have a significant impact on internal and external networking, as well as entrepreneurial orientation. However, internal networking has a positive but non-significant effect on entrepreneurial orientation. On the other hand, entrepreneurial orientation significantly influences new venture performance. Therefore, this research also discusses the practical implications of the important role of business incubator resources in assisting new ventures to grow rapidly.